The development of affective assessment instruments in the new normal era (post-covid-19) - Mu'ammar, Muhammad Arfan; Sofandi, Aris (IAIN Salatiga, 2022)
This development research was conducted at MTs Ma'arif Ketegan Sidoarjo. The types of data obtained are qualitative and quantitative data. The survey results showed that 50% of teachers developed their own affective assessment instruments but 87.5% of teachers admitted that these instruments were not valid and reliable. Then as many as 81.3% of teachers chose to use the observation method in assessing student effectiveness during online learning, because it is considered the easiest. As many as 62.5% of teachers do not understand that affective assessment of students in online learning can be done using the self-assessment method. The instrument is presented in a Google Form which contains 50 contextual statement points with a Likert Scale. The content validation score with the Aiken's V formula obtained a score of less than 1 for each statement item. Construct validation is a follow-up to the input of the supervisor and the theory that has been analyzed. External validation shows an increase in instrument models that are more applicable and adaptive. Instrument stability obtained a score of 0.885 so it was concluded that it was less reliable for a significant level of 1% and reliable for a significant level of 5%. The instrument equivalence data shows that there is no significant change in the results of the original and alternative instruments. Internal consistency with the Cronbach Alpha coefficient obtained a score of 0.92 with a very high category. The instrument also has a practical and efficient title. Thus this instrument is considered valid, reliable, useful, and valid. The response given by this instrument is said to be valid, reliable, practical and valid.